Space weathering on the Moon: Farside-nearside solar wind precipitation asymmetry. (February 2019) - Kallio, E.; Dyadechkin, S.; Wurz, P.; Khodachenko, M.
Abstract: The lunar surface is continuously under the impact of solar wind plasma, which breaks the chemical bonds of the surface material resulting in weathering of the surface and a modified chemical composition. Ion impact also sputters the surface material, affecting the composition of the lunar exosphere, and it controls the electrical properties of both the lunar surface and the near surface space. We have studied the lunar farside-nearside (FN) hemispherical asymmetry of the solar wind proton impact on the lunar surface along the orbit of the Moon during fast solar wind conditions. The analysis is based on a 3D hybrid model where ions are accelerated by the macroscopic j × B and pressure gradient forces. The derived proton impact surface map shows that the highest cumulative solar wind proton addition on the lunar surface is located on the farside while the most energetic protons precipitate on the nearside. The total ion impact rate was found to be smallest when the Moon is deep in the magnetotail. The total ion impact rate on the lunar surface varies while the Moon orbits the Earth and these longitudinal variations are caused by the magnetosphere and lunar tidal locking. Highlights: Solar wind precipitation on the Moon calculated by a 3D j×B hybrid model. Proton precipitation has a cumulative farside-nearside asymmetry: The ion flux is smaller but more energetic on nearside. Asymmetry is a consequence of lunar tidal locking and shielding of the magnetosphere